The Mechanism of Preparation on Purwodadi Botanical Garden Unit Towards Remuneration (Study at Purwodadi Botanical Garden Office-Pasuruan Regency) - Novia Putri Andriani M. (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract In 2011, the whole Ministry, Agencies and the Local Government has been targeted a commitment to implement the process of bureaucratic reform.Therefore, one of the unit below the unit of LIPI Purwodadi Botanical Garden in 2011 began to prepare Bureaucratic Reform which will have an impact on remuneration. The purpose of this study is to describe and analyze the mechanism of preparation Purwodadi Botanical Garden Unit toward remuneration and supporting and inhibiting factors. This study used descriptive methods and qualitative approach. The results of this study are the mechanism of preparation consist of: socialization, submission document Road Map and remuneration, implement bureaucratic reform at 7 area changes, valuation/evaluation of bureaucratic reform.In preparation remuneration almost finished, but there are few problems that occur inhibiting factors such as heterogeneous understanding of employee. The suggestion given are doing sustainably socialization and giving training to improve the work culture of employee. Keywords: Bureaucratic Reform, Remuneration Abstrak Pada tahun 2011, keseluruhan Kementerian, Lembaga dan Pemerintah Daerah telah ditargetkan memiliki komitmen untuk melaksanakan proses reformasi birokrasi. Oleh karena itu, salah satu unit di bawah LIPI yaitu Kebun Raya Purwodadi, pada tahun 2011 mulai mempersiapkan Reformasi Birokrasi yang akan berdampak pada remunerasi. Tujuan dari penelitian ini untuk mendeskripsikan dan menganalisis mekanisme penyusunan Satuan Kerja Kebun Raya Purwodadi menuju remunerasi serta faktor pendukung dan penghambat. Penelitian ini menggunakan metode deskriptif dan pendekatan kualitatif. Hasil dari penelitian ini adalah mekanisme persiapan terdiri dari: sosialisasi, penyerahan dokumen Road Map dan remunerasi, menerapkan reformasi birokrasi di 7 area perubahan, penilaian/evaluasi reformasi birokrasi. Dalam remunerasi persiapan hampir selesai, tetapi ada beberapa masalah yang terjadi faktor penghambat seperti pemahaman karyawan yang heterogen. Saran yang diberikan adalah melakukan sosialisasi secara berkelanjutan dan memberikan pelatihan untuk meningkatkan budaya kerja karyawan. Kata Kunci: ReformasiBirokrasi, Remunerasi